Project Based Learning Models Impact on Geography Learning During Pandemic: An Experimental Research - Nada Salym; Nihla Syafira (Jurnal Pendidikan Geografi Undiksha, 2023)
This research is focused on a study that uses an online project based learning model viewed from student's interest in learning geography. The study aimed to see how distance learning affected students' creative thinking skills. Quasi-experimental research methodology is employed in this study using a pretest-posttest control group design. Students from Malang's XI Social Science State Senior High School 9 served as the study's participants. Determine the control class and the experiment is determined with the help of a random generator. As the experimental class, class XI Social Science 2 was used, and class XI Social Science 1 was used as the control class. Data collection techniques utilizing creative thinking ability test sheets and student learning interest questionnaire sheets. Statistical analysis used was the Mann-Whitney test and Two Way Anova test with the help of SPSS 26.0 for Windows. The findings reveal that (1) the project-based learning model had an effect on students' ability to think creatively with a value of asymp sig. (2-tailed) 0.005 < 0.05. (2) the project-based learning model has an impact on creative thinking abilities viewed from students' interest in learning with sig. 0.037 < 0.05.